PENGEMBANGAN MEDIA LECTUREMAKER DALAM PEMBELAJARAN KIMIA SMA POKOK BAHASAN IKATAN KIMIA MELALUI PENERAPAN PROFESSIONAL LEARNING COMMUNITY - Ajeng Gentry Pangastuty; Ucu Cahyana; Agung Purwanto (LPPM Universitas Negeri Jakarta, 2013)
This study aims to provide an alternative media learning chemistry more interesting by generating LectureMAKER through the implementation of Professional Learning Community on the subject of class X Chemical Bonding semester in high school. The method used is the method of research and development (research and development). LectureMAKER development phase of this research include: needs analysis, instructional media development done in collaboration with teachers, due diligence products and product revisions. LectureMAKER development outcomes assessed by the assessment of materials and media, and also by students and teachers. The results of the analysis of test LectureMAKER obtain adequate assessment of the team of experts, teachers, and students. The results of this study indicate that LectureMAKER through the implementation of Professional Learning Community at the Institute of Chemistry, developed the material is good and worthy to serve as an alternative medium of learning in learning CHEMICAL SMA and equal to the class X. Keywords: LectureMAKER, Chemical Bonding, Professional Learning Community, Research and Development